OPPORTUNITIES FOR UTILIZING INTERNATIONAL EXPERIENCES IN ORGANIZING PAYROLL ACCOUNTING WITH EMPLOYEES (World Economics and Finance Bulletin, 2025)
This article highlights the opportunities for utilizing international experiences in organizing payroll accounting with employees. In particular, the payroll systems of the United States, Japan, France, and Germany have been studied and analyzed.